2011
DOI: 10.1007/s12011-010-8948-y
|View full text |Cite
|
Sign up to set email alerts
|

Trace Elements in the Hair of Hemodialysis Patients

Abstract: Trace element disturbance is often observed in hemodialysis patients. While trace element concentrations have been reported in blood samples from hemodialysis patients, they have not been well investigated in scalp hair. In the present study, 22 trace elemental concentrations were measured by inductively coupled plasma-atomic emission spectrometry in the scalp hair of 80 male hemodialysis patients and compared with those of 100 healthy male subjects. In hemodialysis patients, the concentrations of beryllium, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
22
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 31 publications
3
22
1
Order By: Relevance
“…However, the study concerning the levels of different elements in hair of haemodialysis patients revealed that the statistically significant increase in iron was accompanied with a slight decrease in lithium [44]. In the present study, serum iron as well as mean corpuscular haemoglobin was slightly decreased in the lithium-treated group, and selenium co-administration seemed to exert a slight beneficial effect.…”
Section: Discussioncontrasting
confidence: 45%
“…However, the study concerning the levels of different elements in hair of haemodialysis patients revealed that the statistically significant increase in iron was accompanied with a slight decrease in lithium [44]. In the present study, serum iron as well as mean corpuscular haemoglobin was slightly decreased in the lithium-treated group, and selenium co-administration seemed to exert a slight beneficial effect.…”
Section: Discussioncontrasting
confidence: 45%
“…D Van Renterghem et al, had demonstrated elevated concentrations of cadmium in the sera of five patients who were on haemodiafiltration [31]. Bing Chen et al, who studied the whole blood and serum samples of stable Chinese chronic renal failure patients (n=81), haemodialysis patients (n=135), posttransplant patients (n=60) and subjects with normal renal functions (n=42), found a high prevalence of elevated cadmium levels in the haemodialysis patients [33].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, higher arsenic concentrations were found in the serum and the packed cells of patients who had a greater degree of chronic renal insufficiency [30]. A recent study demonstrated that the arsenic level in hair was significantly higher in the haemodialysis patients, as compared to that in healthy subjects [31].…”
Section: Resultsmentioning
confidence: 99%
“…10,15) Furthermore, renal disorders and hypertension, which are most common complications associated with diabetes, affect the levels of elements in the hair of diabetic subjects. [14][15][16]29) Detail studies focused on age and gender, in addition to the renal disorders and hypertension, are necessary to elucidate fully the changes in the concentrations of element in the scalp hair.…”
Section: Discussionmentioning
confidence: 99%
“…However, some data for Mn and Mg previously reported in relation to diabetic subjects were controversial, 1) and nephropathy and hypertension, which are common complications of diabetes, affect the level of trace elements in the scalp hair. 8,[14][15][16] There is no report on the correlation between HbA1c and the concentrations of essential and toxic metals in the scalp hair so far. In the present study, we investigate the relationships between HbA1c and the concentrations of 12 elements (Ca, Mg, Zn, Cu, Fe, Cr, Mn, V, As, Cd, Hg and Pb) in the scalp hair and between HbA1c and eGFR of diabetic patients in Japan.…”
mentioning
confidence: 99%